Learning for Pregnant Women About Giving Colostrum to Newborns at the Cimone Health Center, Tangerang City - Lilik Susilowati; Ella Nurlelawati; Laurentia Dewi (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
The purpose of this study was to determine the factors associated with the administration of colostrum to newborns at the Cimone Health Center, Tangerang City, Banten Province. This study uses a type of observational analytic research. The research method used is cross sectional. The population used in this study were women giving birth normally at the Cimone Health Center, totaling 56 people in October 2020. This research used an accidental sampling technique. The results of a statistical study using chi-square showed that the variables of knowledge and family support were related to the administration of colostrum to newborns with a p-value of (0.001 < α (0.05) and (0.004 < α (0.05), so it can be concluded that mothers with good knowledge have a greater chance of giving colostrum than mothers with less knowledge, and mothers with family support have a greater chance of giving colostrum than mothers with unsupportive family support